COMPARATIVE EVALUATION OF THE EFFECTIVENESS OF TREATMENT METHODS FOR RATED PHENYL HYDRAZINE-HEMOLYTIC ANEMIA IN RATS - Satullaeva Aziza Nietulla kizi (Bright Mind Publishing, 2025)
The aim of the study was a comparative assessment of the effectiveness of the new Reomannisol blood substitute on the state of peripheral blood and bone marrow parameters in experimental hemolytic anemia. Materials and methods. Studies were conducted on 120 outbred white sexually mature male rats. Of the total number of rats, 100 animals were injected with a 2% solution of phenylhydrazine at a dose of 50 mg / kg of animal weight once intraperitoneally to simulate hemolytic anemia (one day). Then, on day 1 of the experiment, the studied animals (n = 120) were randomly divided into five groups, depending on the treatment. In all groups of animals, the dynamics of hemogram indicators was studied. Results. Analysis of the dynamics of hemogram indices in rats with phenylhydrazine hemolytic anemia during treatment showed the high efficiency of the new domestic blood substitute Reomannisol, which contributed to a significant restoration of the reactivity and functional reserves of erythron in rats, which resulted in an increase in the level of hemoglobin, erythrocytes and reticulocytes.
Keywords: Hemolytic anemia, phenylhydrazine, hemogram indices, treatment.